1996
DOI: 10.1002/(sici)1097-0061(199605)12:6<541::aid-yea935>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of a variant of human single-chain urokinase-type plasminogen activator without an N-glycosylation site in the methylotrophic yeast, Pichia pastoris and characterization of the secreted product

Abstract: Human single‐chain urokinase‐type plasminogen activator without an N‐glycosylation site (scu‐PA‐Q302) was produced in the methylotrophic yeast, Pichia pastoris using the shortened prepeptide sequence of a fungal aspartic proteinase, Mucor pusillus rennin (MPR). The level of urokinase‐type plasminogen activator (u‐PA) immunoreactive material in YPM medium was 0·47 mg/l; however, most of the secreted product had been processed to smaller polypeptides. The N‐terminal amino acid sequence of major species was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…AOX1-deleted transformants could grow slowly in the methanol medium because they had another alcohol oxidase encoded by the AOX2 gene, which is expressed more weakly than the AOX1 gene . The frequency of AOX1 disruption by double crossing-over (37%) was identical to the frequency reported for the production of hepatitis B antigen by Cregg et al (1987), tumour necrosis factor by Sreekrishna et al (1989) and human single-chain urokinase-type plasminogen activator (Tsujikawa et al, 1996).…”
supporting
confidence: 77%
“…AOX1-deleted transformants could grow slowly in the methanol medium because they had another alcohol oxidase encoded by the AOX2 gene, which is expressed more weakly than the AOX1 gene . The frequency of AOX1 disruption by double crossing-over (37%) was identical to the frequency reported for the production of hepatitis B antigen by Cregg et al (1987), tumour necrosis factor by Sreekrishna et al (1989) and human single-chain urokinase-type plasminogen activator (Tsujikawa et al, 1996).…”
supporting
confidence: 77%
“…The addition of Triton X-114 during rPIN-a (recombinant puroindoline-a) fermentation increased the production yield of the protein by 10-fold to 13 mg/l and inverted the ratio between secreted and membane-bound rPIN-a [46]. The addition of 0.01% (v/v) Triton X-100 to a feeding medium reduced partially the proteolysis of a urokinase-type plasminogen activator and increased the secretion level [47].…”
Section: Medium Compositionmentioning
confidence: 99%
“…For expression in P. pastoris there is no general rule concerning the need of N-glycosylation for efficient secretion. Indeed, secretion efficiency of a-Nacetylgalactosaminidase is strongly decreased when the Nglycosylation is missing [110], but Tsujikawa et al [111] reported secretion of a variant of human single-chain urokinase-type plasminogen activator without an N-glycosylation site. The gal-T1 produced by P. pastoris is recognized directly by polyclonal antibodies and when analyzed on SDS-PAGE it comigrates with the human gal-T1 indicating that no hyperglycosylation takes place (Malissard et al unpublished results).…”
Section: Galactosyltransferasesmentioning
confidence: 99%